Variable speed induction motors' fault detection based on transient motor current signatures analysis: A review. (1st February 2023) - Yakhni, Mohammad F.; Cauet, Sebastien; Sakout, Anas; Assoum, Hassan; Etien, Erik; Rambault, Laurent; El-Gohary, Mohamed
Abstract: Induction motor is a major component in the industrial sector. It is experiencing great development concerning size, market share, and technological design. Any sudden failure in this element may lead to great damage. Condition monitoring is a fast emerging technology for the online detection of induction motor incipient faults. It avoids unexpected failure of a critical system, by increasing the life expectancy of the concerning elements while reducing operation and maintenance costs. This paper presents the condition monitoring techniques used with these machines, focusing on the Transient Motor Current Signatures Analysis method that has proven its effectiveness in diagnosing faults of electrical rotating machines, gathering a review on the most important applications that can be used with this technology, and how to process these signals to find out the type and cause of the fault. What distinguishes this paper is that it focuses on applications with variable speeds, so two promising techniques that will be effective in non-stationary signals frequency estimation are presented, which are the Adaptive Notch Filtering method and the Adaptive-Observer approach. Challenges and future goals are also discussed to guide researchers wishing to delve into this field. Highlights: Induction motors are exposed to electrical and mechanical faults. The Condition Monitoring Techniques used to predict these errors are presented. Focusing on the Transient Motor Current Signatures Analysis method. This paper focuses on applications with variable speeds. Adaptive Notch Filtering method and the Adaptive-Observer approach are used.